Aktivitas antioksidan, total polifenol, total flavonoid, dan sifat sensoris inovasi tempe kedelai dengan substitusi tepung daun kelor - Kukuk Yudiono (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
One of our nation's original fermented products using soybean raw materials is Tempeh. Tempeh has been known as an inexpensive source of vegetable protein but tempeh also contains micronutrient compounds that play an important role in body health. To increase the content of micronutrient compounds such as polyphenols and flavonoids which are known as sources of antioxidants, in this study Moringa leaf flour was added in the process of making tempeh. The purpose of this study was to determine how much the content of polyphenols, flavonoids and antioxidants in tempeh might increase with the addition of Moringa leaf flour. One factor experimental design was used, with the percentage of Moringa leaf flour (0 %, 3 %, and 6 %) as treatment. The observed variables: antioxidant activity (%), total polyphenols (mg GAE/g extract) and total flavonoids (µg/g). The antioxidant test results of tempe substituted with Moringa leaf flour (3 %) and (6 %) were (85.156 % and 93.67 %) higher than without the addition of Moringa flour which was only (68.166 %). To test the total polyphenols in tempe substituted with Moringa leaves (3 %) and (6 %) were (29.24 and 49.52 mg GAE/g extract) or 2-3.5 times the total polyphenols in tempe without Moringa leaf flour which only of (14.15 mg GAE/g extract). While the total flavonoid yields were: a) soybean tempeh without innovation of moringa leaf flour 642.19 (µg/g), b) soybean tempeh with innovation of 3 % Moringa leaf flour was 798.70 (µg/g), and c) soybean tempe with 6 % Moringa leaf flour innovation is 904.97 (µg/g). In conclusion, the antioxidant activity, total polyphenols, and total flavonoids in the tempeh with the addition of moringa leaf flour increased above 100 %. In the descriptive organoleptic test, the panelists gave positive impressions for the parameters of cohesiveness, texture, taste, and aroma, except for the color of the tempeh